2006
DOI: 10.2174/138161206778743510
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of TLR-Mediated Innate Immune Responses by Peptidoglycans through NOD Signaling

Abstract: Toll-like receptors (TLRs) recognize common motifs, pathogen-associated molecular patterns (PAMPs), in microorganisms. Bacterial PAMPs are mainly distributed on cell-surfaces. Peptidoglycans (PGNs) are ubiquitous constituents of bacterial cell walls. Muramyldipeptide (MDP; N-acetylmuramyl-l-alanyl-d-isoglutamine) is a common and key structure of PGNs and exhibits most the of bioactivities of PGNs. Recently, the intracellular receptor for MDP was revealed to be NOD2. Another bioactive moiety of PGNs, diaminopim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 52 publications
1
41
0
Order By: Relevance
“…Consistent with the knowledge that TLR2 and NOD2 pathways act synergistically on human B lymphocytes (28) and DCs (29) to induce immune responses, as well as our in vitro data, the strong adjuvant effect observed in vivo is probably due to the induction of inflammation at the injection site, which leads to the recruitment of APCs such as macrophages and DCs. The latter are able to uptake Ag carried by PLA NPs and then migrate to draining lymph nodes to present Ag to naive T cells.…”
Section: Nod2/tlr2 Chimeric Ligand Enhances Systemic and Mucosal Immusupporting
confidence: 91%
“…Consistent with the knowledge that TLR2 and NOD2 pathways act synergistically on human B lymphocytes (28) and DCs (29) to induce immune responses, as well as our in vitro data, the strong adjuvant effect observed in vivo is probably due to the induction of inflammation at the injection site, which leads to the recruitment of APCs such as macrophages and DCs. The latter are able to uptake Ag carried by PLA NPs and then migrate to draining lymph nodes to present Ag to naive T cells.…”
Section: Nod2/tlr2 Chimeric Ligand Enhances Systemic and Mucosal Immusupporting
confidence: 91%
“…NOD1 senses diaminopimelic acid-containing peptidoglycan present in Gram-negative bacteria, whereas NOD2 senses the muramyl dipeptide present in most organisms. Because of the apparent lack of direct effects on cell signaling induced by activators of NLRs, it is suggested that their role in pathogen sensing is one of cooperation with the TLRs (107). However, studies suggested that the actions of NOD1 vary between cell types and, unlike those seen with LPS, the in vivo effects may be independent of leukocyte activation.…”
Section: Nlrs and Alimentioning
confidence: 99%
“…Synthetic NOD1 agonists stimulate chemokine production and neutrophil recruitment in vivo (Masumoto et al 2006), but alone are ineffective in activating monocytic cells in vitro (van Heel et al 2005). Because of the apparent lack of direct effects on cell signalling induced by activators of NLRs, it is suggested that their role in pathogen sensing is one of co-operation with the TLRs (Takada & Uehara 2006). However, data from our group suggest that the actions of NOD1 vary between cell types and, unlike those seen with LPS, the in vivo effects may be independent of leukocyte activation.…”
Section: Nod Receptorsmentioning
confidence: 99%